Extrusion of dough in ring lubricating layer - Брылёв, Евгений Анатольевич; Яцук, Анна Леонідівна (Technology audit and production reserves, 2014)
Abroad there are developments in which the highly viscous mass conveyed in the pipe surround the circular casing of a low viscosity fluid, thereby reducing friction. In this regard, it seems urgent to develop design of macaroni presses, in which the resistance movement test in the press matrices was minimized, which improves the efficiency of their work, as well as performance. The purpose of research is to solve the problem of non-contact forming pasta - based research and development of a fundamentally new method and apparatus according to contemporary pasta production. Basic analytical problems were solved using the theory of hydrodynamic flow in thin layers, namely the theory of gas lubrication. The contactless molding pasta method reduces friction to nearly zero in the matrices of the pasta press. The research results can be applied in the design of pasta presses using matrices with porous inserts.